MicroRNAs as noninvasive biomarkers for the diagnosis and prognosis of liver fibrosis in HCV genotype 4 patients - Abdel-Al, Amanda (AUC Knowledge Fountain, 2017)
Hepatitis C virus (HCV) is a major world health problem affecting millions of people worldwide. HCV causes fibrosis of the liver; untreated, it leads to complications such as hepatic cirrhosis, decompensation, and hepatocellular carcinoma (HCC). Current methodologies used to determine the progression of hepatic fibrosis rely heavily on liver biopsy, a dangerous and invasive procedure, with subjective analysis of the results of the biopsy. Liver biopsies are also difficult to perform in the developing world, where the strain of HCV infection is great. A new methodology, that is both convenient and inexpensive, is needed for monitoring the progression of liver fibrosis in HCV patients. Small noncoding RNAs known as microRNAs are up-regulated or down-regulated when damage occurs in the liver. miRNAs are stable and present in almost all body fluids, therefore the measurement of circulating miRNAs in serum of liver fibrosis as a noninvasive method to evaluate disease severity and progression is promising. Currently, miRNAs have been found to play essential roles in hepatic stellate cell (HSC) differentiation, proliferation, apoptosis and migration linking them to aberrant expression variations in the development of liver fibrosis. Several microRNAs have shown promise as noninvasive biomarkers of hepatic fibrosis, and some even in the treatment of HCV. To study regulation of genes at the miRNA level is a huge advantage as gene expression is regulated at an epigenetic level before even the formation of proteins. Hepatitis C-genotype 4 infected patients were selected to detect and study the progression of liver fibrosis. The study consisted of three patient groups: 42 cases of chronic hepatitis C (CHC) with early stage fibrosis, 45 cases of CHC with late stage fibrosis, and 40 healthy patients with no CHC or fibrosis as controls. Blood samples were taken from each patient and RNA was extracted using the miRNeasy extraction kit. Expression patterns of 5 miRNAs (miR-16, miR-146a, miR-214-5p, miR-221, miR-222) were measured in each group using TaqMan real-time reverse transcription-polymerase chain reaction. MiRNA analysis was performed to determine the most specific and sensitive miRNA to be used as a diagnostic biomarker. Serum levels of miRNA-16, miRNA-146a, miRNA-221, and miRNA-222 were all significantly upregulated in early and late stage fibrosis compared to the control (p<0.001). MiRNA-222 had the highest sensitivity and specificity values in both early and late stage fibrosis with values of (69.23 %, 83.83%) and (100%, 96.77%) respectively. MiRNA-221 had the second highest sensitivity and specificity values with the late stage fibrosis group having values of 100% and 88.24% respectively. MiRNA-222 and miRNA-221 suggest promising potential as biomarkers for HCV-induced liver fibrosis as they had the highest sensitivity and specificity values. MiRNA-221 showed significant positive correlations with both miRNA-16 and miRNA-146a in the early and late stage fibrosis groups, with the early stage having a stronger correlation (at the 0.01 level). These correlations have great substantial values for future uses in formulating liver fibrosis diagnostic assays.